2019
DOI: 10.3390/ma12182915
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of High-Tc Superconducting Bulk using Different Jc–T Relationships over Dynamic Permanent Magnet Guideway

Abstract: The linear temperature dependence of critical current density Jc∝((Tc-T)/(Tc-T0)) and the nonlinear functions of Jc∝(1-(T/Tc)2)α with the exponent α equal to 1, 3/2, and 2 are used to calculate the dynamic levitation force, the temperature distribution, and the current density distribution of the high-temperature superconducting (HTS) YBaCuO bulk over a permanent magnetic guideway (PMG). The calculations were based on the H-formulation and E–J power law. The model of the HTS bulk and the PMG has been built as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…J c is also related to the temperature T of the bulk superconductor [34]. We analyze the heat loss inside the bulk superconductor through the following three equations, which are solved in COMSOL using the heat transfer interface [25,26]:…”
Section: Hts-pmg Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…J c is also related to the temperature T of the bulk superconductor [34]. We analyze the heat loss inside the bulk superconductor through the following three equations, which are solved in COMSOL using the heat transfer interface [25,26]:…”
Section: Hts-pmg Modelmentioning
confidence: 99%
“…This method can reflect the electromagnetic characteristics of HTS material. In recent years, the H formulation for solving the HTS-PMG model has been popular because of its easy implementation in COMSOL software [23][24][25]. Hong et al [26] studied the dynamic electromagneticthermal effect of the HTS bulk at high speed under different E-J constitutive laws by the H method.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the limitation of experimental conditions, the behavior of an HTS maglev vehicle on a curve is simulated by rotating the circular PMG and fixing the HTS bulks. This means that the varying rotational speed can only lead to a lowfrequency change of the alternating magnetic field on the bulk superconductors [31] but not to the centrifugal effect of the HTS bulks. Previous studies have shown that the energy loss of the HTS bulk is independent of frequency at low frequency, and magnetic hysteresis is the major cause [27,32].…”
Section: Influence Of the Mld On Dynamic Guidance Forcementioning
confidence: 99%
“…Other than the fact that H-formulation should work, there is a very large literature of its successful application to problems in HTS machines modelling. Overall, the H-formulation has been used in studying topics such as: ac loss [86], dynamic resistance [87], pulse magnetisation of bulks [88], demagnetisation of bulks [89], magnetic levitation [90], and many more. A modern review of such H-formulation applications can be found in [91].…”
Section: Why H-formulationmentioning
confidence: 99%